Pengaruh Pelayanan dan Kualitas Produk terhadap Keputusan Pembelian Produk Kosmetik YOU di Toko Duta Cosmetic Bireuen - Bunaiya, Riza; Nova, Nova; Erfansyah, Muhammad (Aceh Cooperative Care, 2024)
The research aims to analyze the influence of service quality and product quality on product purchasing decisions. By studying YOUR cosmetic products at the Duta Cosmetic shop in Bireuen City. The research is a survey using a questionnaire instrument on a sample of 96 consumers using a purposive sampling method. Analysis was carried out using a statistical approach through multiple linear regression models and data were analyzed using SPSS version 25.0 software. By concluding that the instrument's validity and reliability are guaranteed, hypothesis testing is carried out to determine the influence between variables in the regression model. The results prove that service quality and product quality together have a significant influence on purchasing decisions, with a contribution of 76.2%. Partially, both factors, both service quality and product quality, have a significant influence on purchasing decisions